Sabun Padat Transparan Ekstrak Etanol Kayu Secang (Caesalpinia Sappan L.) - Devina Chandra; Natanael Priltius; Manuppak Irianto Tampubolon (Lembaga Pengembangan Kinerja Dosen, 2023)
Secang wood from the Caesalpiniacea tribe which was commonly found in Indonesia had secondary metabolites as antibacterial. This study aims to formulate secang wood ethanol extract into a transparent solid soap that is able to meet quality requirements. This research method was begin with formulating the extract into a transparent solid soap preparation with 3 concentrations, namely 5g (F1), 10g (F2), and 15g (F3). Furthermore, appearance tests, foaming ability, free alkali, free fatty acids, irritation, hedonic, and pH were carried out. The results of the research on transparent solid soap gave different colors for each concentration, namely transparent bright red (F1) and transparent dark red (F2 and F3) which were stable for 4 weeks; the foam power test shows a height of 4.5-6.5 cm after 10 minutes; free alkaline test shows a value of 0.07-0.08%; free fatty acid test 0.16%, and pH test 8.96-9.66 at week 4; and transparent solid soap does not cause irritation, attractive and liked by volunteers